Cognitive impairment at older ages among 8000 men and women living in Mexico City: a cross-sectional analyses of a prospective study - González-Carballo, C; Kuri-Morales, P; Chiquete, E; Rojas-Russell, M; Santacruz-Benitez, R; Ramirez-Reyes, R; Garcilazo-Ávila, A; Berumen, J; Trichia, E; Friedrichs, LG; Orellana, P; Ochoa-Rosales, C; et al. (BioMed Central, 2024)
Background: There is limited population-based evidence on the prevalence of cognitive impairment in Mexico, a country with a rapidly aging population and where key risk factors, such as diabetes and obesity, are common. This study describes the distribution of cognitive impairment in adults from Mexico City. Methods: This cross-sectional population-based study included participants from the Mexico City Prospective Study which recruited 150,000 adults aged ≥ 35 years in 1998–2004. In 2015–2019 about 10,000 survivors were resurveyed with identical information from the original survey and additional assessments including a cognitive assessment. The main analyses included those aged 50–89 years with complete cognitive assessment and covariate data at resurvey. Cognitive impairment was defined by a score ≤ 24 on the Mini Mental State Examination (MMSE). The distribution of MMSE scores and cognitive impairment by age, sex, and major disease risk factors (diabetes, hypertension, and adiposity) was analyzed among those with complete MMSE data and some degree of self-reported formal education. Results: Of the 9,288 participants aged 50–89 years at the 2015–2019 resurvey with complete data, 8,197 reported having at least some years of formal education. Among these (mean age 66 years; 31% men), their mean MMSE score was 26.2 (SD 3.6) points, 1,941 (24%) had cognitive impairment, their mean body-mass index (BMI) was 28.6 (SD 5.5) kg/m2, 3,008 (37%) had hypertension and 2,467 (30%) had diabetes. The sex- and district-standardised prevalence of cognitive impairment increased strongly with age, from 10% in those 50–59 years to 55% in those aged 80–89. At any given age, the prevalence of cognitive impairment was higher in women than in men. After accounting for the effects of age, sex, and district there was little difference in the prevalence of cognitive impairment between participants with or without diabetes, hypertension, overweight or obesity (BMI ≥ 25 km/m2), or high levels of fat mass. Conclusions: In this population of adults aged 50–89 years from Mexico City, the prevalence of cognitive impairment was high, particularly among women. The extent to which cognitive impairment relates to health outcomes in this population needs to be investigated.